2018
DOI: 10.4103/japtr.japtr_320_18
|View full text |Cite
|
Sign up to set email alerts
|

Usability testing of bed information management system: A think-aloud method

Abstract: Not considering the usability in designing clinical information systems causes problems in human–computer interaction and patient dissatisfaction. Therefore, in this study, the usability of the bed information management system (BIMS) was examined by think-aloud method. This cross-sectional study was conducted on the BIMS in 50 noneducational hospitals. Participants consisted of three groups including users, facilitators, and technical support. To carry out the study, a scenario consisting of four tasks was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Statements and observations were mapped deductively to the four main determinants of UTAUT as the main categories. Subsequently, inductive subcategories were grouped within these categories and assigned to the eight PCM core components [47,48]. As a result, a comprehensive coding framework evolved.…”
Section: Discussionmentioning
confidence: 99%
“…Statements and observations were mapped deductively to the four main determinants of UTAUT as the main categories. Subsequently, inductive subcategories were grouped within these categories and assigned to the eight PCM core components [47,48]. As a result, a comprehensive coding framework evolved.…”
Section: Discussionmentioning
confidence: 99%
“…In the critically important field of health prevention, where engaging the target population poses significant challenges [ 17 , 18 ], testing and refinment of usability is paramount [ 19 ]. The high contextuality of mHealth interventions prevents the exact transferability of results from comparable studies in this topic and must be carried out individually [ 19 , 20 ] Consequently, usability testing, regardless of the results, should be considered valuable [ 21 , 22 ] and involving the potential target group in the development process can increase acceptance of mHealth apps [ 19 , 23 ]. No matter how well informed experts are about a certain topic, the integration of the target group into the development process is inevitable [ 12 ].…”
Section: User Participation and Usabilitymentioning
confidence: 99%
“…No matter how well informed experts are about a certain topic, the integration of the target group into the development process is inevitable [ 12 ]. Various studies have already shown that usability testing of mHealth apps can contribute not only to an improvement of usability itself, but also in content of the app [ 22 , 24 ]. As in comparable studies, the think-aloud method (TA) was mainly used here to investigate usability [ 12 ].…”
Section: User Participation and Usabilitymentioning
confidence: 99%